2019
DOI: 10.1111/pce.13549
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved dissection of the molecular crosstalk driving Fusarium head blight in wheat provides new insights into host susceptibility determinism

Abstract: Fungal plant diseases are controlled by a complex molecular dialogue that involves pathogen effectors able to manipulate plant susceptibility factors at the earliest stages of the interaction. By probing the wheat–Fusarium graminearum pathosystem, we profiled the coregulations of the fungal and plant proteins shaping the molecular responses of a 96‐hr‐long infection's dynamics. Although no symptoms were yet detectable, fungal biomass swiftly increased along with an extremely diverse set of secreted proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 91 publications
5
44
0
Order By: Relevance
“…Many other studies have also identified F. graminearum genes involved in pathogenicity and some appeared to have only a quantitative effect (i.e., aggressiveness-related genes) (Pariaud et al, 2009). These genes encode secreted proteins and effectors that may play roles in the infection course (Krijger et al, 2014;Lu and Edwards, 2015;Chetouhi et al, 2016;Fabre et al, 2019). Furthermore, previous genomics studies have identified more than 600 genes coding for secreted proteins (Brown et al, 2012;King et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies have also identified F. graminearum genes involved in pathogenicity and some appeared to have only a quantitative effect (i.e., aggressiveness-related genes) (Pariaud et al, 2009). These genes encode secreted proteins and effectors that may play roles in the infection course (Krijger et al, 2014;Lu and Edwards, 2015;Chetouhi et al, 2016;Fabre et al, 2019). Furthermore, previous genomics studies have identified more than 600 genes coding for secreted proteins (Brown et al, 2012;King et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous genomics studies have identified more than 600 genes coding for secreted proteins (Brown et al, 2012;King et al, 2015). Some have been identified at the proteome level (Lowe et al, 2015;Fabre et al, 2019) suggesting that F. graminearum could synthesize a large number of proteinous effectors.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of these is provided in Table 2. (Yang et al 2012) or secreted proteins present both in planta and in vitro (Fabre et al, 2019). Paper et al (2007) identified F.…”
Section: Current Knowledge Of F Graminearum Effector Proteinsmentioning
confidence: 99%
“…CEPs were compared with previously published literature on F. graminearum secretomes/proteomes (Brown et al, 2012;Fabre et al, 2019;Ji et al, 2013;Lu & Edwards, 2016;Lysenko et al, 2013;Paper et al, 2007;Phalip et al, 2005;Rampitsch et al, 2013;Taylor et al, 2008;Yang et al, 2012;W. Zhou et al, 2006) and transcriptomes (Brown et al, 2017;Lysøe et al, 2011;Pan et al, 2018;Qinhu Wang et al, 2017).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation